English Teachers Vs. Non-English Teachers' Voices On University Students' Intercultural Awareness Skills - Melati, Melati; Ulfiati, Lilik; Triyana Safitri, Nyimas (International Journal of Language Teaching and Education, 2023)
This paper describes the perspectives of English teachers and non-English teachers in a university setting about students’ Intercultural Communication skills in the context of English as a foreign language (here after, EFL) in Indonesia. This is analyzed through both English and non-English teachers’ viewpoints regarding their perceptions of Intercultural Communication skills of attitudes, knowledge of social groups and their products and practices in one’s own and in one’s interlocutor’s country, interpreting document or event from another culture, acquiring new knowledge of a culture, cultural practices, operating knowledge, attitudes, skills, and evaluating critically on the basis of explicit criteria perspectives, practices, or products in one’s own and other culture. In this study, eight English teachers and six non-English teachers in a university, Indonesia were involved. From the Focus Group Discussion, this study proved that Intercultural Communication is essential competences in learning English, both from English and non-English teachers viewpoints. The present study is expected to provide comprehensive analysis of what activities or experiences of teaching Intercultural Awareness in EFL environment can be achieved by the students.